2021
DOI: 10.3390/nu13113788
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of COVID-19 Lockdown on Changes in Body Mass Index and Lifestyle among Croatian Schoolchildren: A Cross-Sectional Study

Abstract: Globally, the COVID-19 pandemic altered adults’ and children’s lifestyles and habits, causing an increase in body weight. Adolescents are sensitive to habit changes and, because of their insufficient capacity to deal with the unexpected COVID-19 changes, were at greater risk of noncommunicable disease development due to the consequences of adopting unhealthy habits. The survey aimed to reveal the changes in nutritional status and lifestyle habits of school children in Croatia and to assess their nutrition know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 51 publications
(72 reference statements)
1
19
0
8
Order By: Relevance
“…This means that females had significantly more healthy eating and feeding habits during the epidemic than males. Consistent with our observations, Kenđel Jovanović G et al found that females consumed significantly more olive oils and sweets than males (P-value was 0.047 and 0.002, respectively) while no association was found between gender and fruit and vegetable intake [ 26 ]. Rodríguez-Pérez C reported that males had a significant difference in the consumption of fruits, vegetables and olive oil [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This means that females had significantly more healthy eating and feeding habits during the epidemic than males. Consistent with our observations, Kenđel Jovanović G et al found that females consumed significantly more olive oils and sweets than males (P-value was 0.047 and 0.002, respectively) while no association was found between gender and fruit and vegetable intake [ 26 ]. Rodríguez-Pérez C reported that males had a significant difference in the consumption of fruits, vegetables and olive oil [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with the Italian study by Mattioli, A.V, and colleagues, which states that obesity is likely to be a consequence of quarantine stress attributable to a change in lifestyle and eating habits. Kenđel Jovanović G et al found significant weight gain in Croatian children as the prevalence of obesity in school children increased from 21% before closure to 24% after closure [ 26 ]. In our study, 59 out of 151 children (39.1%) gained weight during closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is important to highlight that the data in our study were collected during the COVID-19 pandemic. Thus, the results may be affected, since during this stage, children have undergone changes that have affected their lifestyle, as evidenced by different existing publications in the literature [ 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…LGBTIQ+ young people were more likely to report symptoms of anxiety and depression, findings echoed in Belgium (albeit amongst adults) where survey research suggests that the pandemic exacerbated mental health disparities by sexual orientation (Just Like Us, 2021 [30]; Reyniers et al, 2022[31]);. A survey of under-18s in the United Kingdom found that ethnic minority young people were significantly more likely to report symptoms of anxiety or depression and have suicidal thoughts than their white counterparts (Kooth, 2021[32]).…”
Section: Figure 15 Young People In Precarious Financial Circumstances...mentioning
confidence: 96%